2019
DOI: 10.1177/1553350619868112
|View full text |Cite
|
Sign up to set email alerts
|

Full Robotic Distal Pancreatectomy: Safety and Feasibility Analysis of a Multicenter Cohort of 236 Patients

Abstract: Introduction. Despite the widespread use of the robotic technology, only a few studies with small sample sizes report its application to pancreatic diseases treatment. Our aim is to present the results of a multicenter study on the safety and feasibility of robot-assisted distal pancreatectomy (RDP). Materials and Methods. All RDPs for benign, borderline, and malignant diseases performed in 5 referral centers from 2008 to 2016 were included. Perioperative outcomes were evaluated. Results. Two hundred thirty-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
3
29
0
1
Order By: Relevance
“…A minimally invasive approach is considered technically available, safe and feasible for DP in the treatment of leftside pancreatic tumors [5,[26][27][28][29]. As an inevitable part of minimally invasive DP, RDP has been frequently analyzed in observational studies, and a series of reports have indicated that RDP results in a shorter operative duration, less blood loss, shorter postoperative hospital stay, higher spleen preservation rate, and comparable morbidity and mortality rates [30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…A minimally invasive approach is considered technically available, safe and feasible for DP in the treatment of leftside pancreatic tumors [5,[26][27][28][29]. As an inevitable part of minimally invasive DP, RDP has been frequently analyzed in observational studies, and a series of reports have indicated that RDP results in a shorter operative duration, less blood loss, shorter postoperative hospital stay, higher spleen preservation rate, and comparable morbidity and mortality rates [30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have looked at clinical outcomes following robotic distal pancreatectomy, these reviews have only been introspective and generally small. 4,[8][9][10][11] The optimal surgical approach to a distal pancreatectomy has been debated since it became apparent that minimally invasive modalities were a viable choice for the skilled surgeon. This manuscript addresses and justifies the role of the robotic platform to complex abdominal operations such as distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 More recently, minimally invasive approaches (eg, laparoscopy) for pancreatic resections have shown tremendous improvements in patient outcomes including shorter lengths of confinement and quicker returns to functional activities. [3][4][5] With laparoscopic approaches becoming broadly adopted, it became indisputable that complex pancreatic and hepatobiliary surgery through minimally invasive techniques was possible; nonetheless, the question remained: is it practical? Unfortunately, laparoscopy has a number of inherent limitations that hinder its application to many complex operations, especially those requiring some form of reconstruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muchas de sus predicciones reflejaban el conocimiento clínico que tendría un cirujano, pero este algoritmo también fue capaz de ajustar frases que describen a los pacientes (por ejemplo, irritado, cansado) en el primer día del postoperatorio para lograr predicciones con una sensibilidad del 100% y una especificidad del 72% 32 . El uso de los robots quirúrgicos, visto anteriormente, es una realidad cotidiana en nuestro medio, sobre todo en cirugía prostática 33 , colorrectal 34 o pancreática 35 al considerarse un método menos invasivo. Además de los desarrollos comerciales existentes, se están desarrollando sistemas de asistencia robótica en cirugía de código abierto como el sistema Raven II que será probado en diferentes universidades estadounidenses 36 .…”
Section: Aplicaciones En Medicinaunclassified